Corrosion behavior of the copperized layer prepared by double glow plasma surface alloying technology in 3.5 wt.% NaCl solution - Yang Zhengang; Liang Wenping; Jia Yanlin; Miao Qiang; Ding Zheng; Qi Yan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
In this paper, the copperized layer was fabricated on the surface of Q235 steel via double glow plasma surface alloying technology to improve the marine fouling organisms attached on the surface of marine structures. The microstructure and phases composition of copperized layer were analyzed by SEM and XRD. The corrosion characteristics of substrate and copperized layer were investigated in 3.5 wt.% NaCl solution. The results indicated that the adhesion stress of copperized layer was strong due to the gradient structure of an outermost deposition layer and inner diffusion layer. The corrosion characteristics of copperized layer were different from substrate. The corrosion products of Q235 steel were mainly β-FeOOH, γ-FeOOH and α-FeOOH in the early stage of corrosion process. Then the whisker-like structure of α-FeOOH grew on the surface of γ-FeOOH, and β-FeOOH transformed into γ-FeOOH to achieve thermodynamically equilibrium. The dissolved copper ions in solution resulted in a unique difference in the formation of corrosion products, which inhibited the transition of iron hydroxide and promoted the formation of amorphous phases. The amorphous phase with few holes and cracks controlled the diffusion of oxygen, which restrained the oxidation-reduction reaction of the iron hydroxide at the bottom of the rust layer.